2015
DOI: 10.1016/j.rboe.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Result from arthroscopic surgical treatment of renewed tearing of the rotator cuff of the shoulder

Abstract: ObjectivesTo evaluate function among patients with postoperative recurrence of rotator cuff injuries that was treated arthroscopically (case series) and compare this with function in patients without recurrence (control group); and to compare function among patients with recurrence of rotator cuff injuries that were greater than and smaller than 3 cm.MethodsThis was a retrospective evaluation of patients who underwent arthroscopic revision of rotator cuff injuries using the ASES, Constant & Murley and UCLA sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 25 publications
(33 reference statements)
0
15
0
4
Order By: Relevance
“… 13 42 One study dealt with results of surgery after failed attempt at repair of irreparable rotator cuff tear 35 and six had insufficient data (ie, no distinction in the results between primary and revision cases). 12 21 29 31 37 39 Two studies described the results 24 and the operative technique 26 of the same population. Finally, 10 met our inclusion criteria and were included in this study ( table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“… 13 42 One study dealt with results of surgery after failed attempt at repair of irreparable rotator cuff tear 35 and six had insufficient data (ie, no distinction in the results between primary and revision cases). 12 21 29 31 37 39 Two studies described the results 24 and the operative technique 26 of the same population. Finally, 10 met our inclusion criteria and were included in this study ( table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…When they occur, re-ruptures impair the functional outcome and the degree of patient satisfaction. 9 In order to improve the coverage area of the insertional footprint of the rotator cuff and decrease the chances of a rupture, a new arthroscopic repair technique with anchors was developed – the double row method. 14 …”
Section: Discussionmentioning
confidence: 99%
“…The integrity of the rotator cuff after its repair is related to postoperative functional results. 9 As lower re-rupture rates have been observed, better clinical outcomes would be expected. However, in addition to Tudisco et al, 5 other authors did not observe differences in clinical scores when comparing these two fixation techniques, as shown in a recently published meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…They are considered reliable, with great internal consistency, good responsivity, and were previously validated. 45 In our study, only one publication (4%) 18 used the ASES scale, and two studies (8%) 15 , 32 used SST for evaluation. On their turn, Makhni et al 9 observed that the publications of the six major international orthopedic journals between 2010 and 2014 used scales considered more reliable; ASES questionnaire was used in 59%, and the SST in 28%.…”
Section: Discussionmentioning
confidence: 90%
“…In the period evaluated, 712 original articles were published in the Brazilian Journal of Orthopedics and 588 in Acta Ortopédica Brasileira, or 1300 publications. Among these, 84 (6.7% of the total) were clinical articles on shoulder diseases; 25 publications (1.9% of the total) 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 evaluated the clinical results of treatment of rotator cuff tears ( Table 1 ); twenty studies (80%) were case series (level of evidence IV), one (4%) case–control study (level of evidence III) and four (16%) cohorts (level of evidence II). No randomized study was published in the period.…”
Section: Resultsmentioning
confidence: 99%